2007
DOI: 10.1002/gepi.20265
|View full text |Cite
|
Sign up to set email alerts
|

Population differences in the International Multi‐Centre ADHD Gene Project

Abstract: ) ascertained from clinics for combined-type attention definity hyperactivity disorder in an offspring. 863 SNPs were successfully genotyped across 47 autosomal genes implicated in psychiatric disorders yielding a single nucleotide polymorphism (SNP) density of approximately one SNP per 2.5 kb. A global test of heterogeneity showed 269 SNPs nominally significant (expected 43). Inclusion of the Israeli population accounted for approximately 70% of these nominally significant tests. Hardy-Weinberg equilibrium te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…32,33 Prior studies have shown that population stratification in Germansare small. 40,86,87 Thus, at the time when SNPs for the follow-up study were chosen, we had not applied a formal test to control for population stratification. A post-hoc principal components analysis (PCA) 88 (EigenSoftv1.01; http://www.genepath.med.harvard.edu/∼reich/Software.htm) and genomic control analysis 42 (showing a lambda of 1.099) had no major impact on the significance level of our 15 SNPs (see Supplementary Online Content, eTable 4), thus confirming these prior obervations.…”
Section: Commentmentioning
confidence: 99%
“…32,33 Prior studies have shown that population stratification in Germansare small. 40,86,87 Thus, at the time when SNPs for the follow-up study were chosen, we had not applied a formal test to control for population stratification. A post-hoc principal components analysis (PCA) 88 (EigenSoftv1.01; http://www.genepath.med.harvard.edu/∼reich/Software.htm) and genomic control analysis 42 (showing a lambda of 1.099) had no major impact on the significance level of our 15 SNPs (see Supplementary Online Content, eTable 4), thus confirming these prior obervations.…”
Section: Commentmentioning
confidence: 99%
“…To ensure the genetic homogeneity of the sample only white Caucasians of European ancestry were included based on information on ethnicity going back to grandparents of the affected sibling pairs. Entry criteria for research assessments were (1) a proband with the ADHD combined subtype, (2) availability of one or more siblings of each affected proband and (3) both the probands and siblings aged between 5 and 17 at the time of assessment, 14 both the children and at least one of their biological parents were available for DNA collection. Eligible families were then invited to the research centers or assessed during home assessments by qualified child psychiatrists or trained interviewers using clinical research assessments.…”
Section: Sample Ascertainment and Diagnosismentioning
confidence: 99%
“…24 Linkage analysis Nonparametric linkage was examined by Merlin using Whittemore and Halpern's S all statistics and Kong and Cox's log of the odds (LOD) score transformation. [24][25][26] Linkage disequilibrium has been shown between tightly linked markers on the Illumina Linkage IV SNP panels 14 and treating them as independent markers can inflate LOD scores. 27 Merlin overcomes this problem by clustering markers that are in LD and estimating the haplotype frequencies to perform multipoint linkage analysis with the composite markers.…”
Section: Genotyping and Data Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…), using DSM-IV criteria [10], Conners rating scale [11,12], Achenbach questionnaire [13] and the Computerized Test of Variables of Attention [14]. All patients underwent a thorough comprehensive evaluation as part of a project on the genetics of ADHD [15]. We excluded participants who were not using the very same (exact) given name in their everyday life.…”
Section: Sampling and Methodsmentioning
confidence: 99%